Republic of Madagascar : First Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2022)
Madagascar continues to be severely affected by the COVID-19 pandemic. After a contraction of GDP estimated at 7.1 percent in 2020, the economic recovery has been sluggish, partly reflecting a delayed reopening of the economy. Postponement of some external budget support, following delays in structural reforms, will open a fiscal financing gap in 2022.